KEEFEKTIVITASAN VIDEOTRON DALAM MENYAMPAIKAN PESAN IKLAN KEPADA MASYARAKAT - Andry Priyadharmadi Purnama; Akbar Abu Thalib (Jurnal Dakwah Tabligh, 2018)
In technology era nowadays, almost all promotion and information media from the company as well as the government switch to print media from visual media. This is because people today prefer to use applied technology for communication and technology. This research aims to review Videotron effectivity on conveying the commercial message to the society. This research was conducted by qualitative description with the primary data sources and secondary. Data was collected by direct observation in Videotron location and interviewed some speaker and Videotron manager in Makassar. Result of this research shows Videotron quite effective to convey a commercial message by giving good visualization. Videotron also become an effective media to present several advertisements on one media therefore can reduce visual trash. In addition, near from traffic light can increase enticement of Videotron that can be a significant strategy to publish the information and attract readers attention. Videotron media has positive impact to the government because of giving a role to to give information about their program and additional aesthetic for the hometown. Implication of this Videotron according society can disturb driver concentration, give strong light and can be hacked by someone.